ENVIRONMENTAL CHOICES VS. COVID-19 PANDEMIC FEAR – PLASTIC GOVERNANCE RE-ASSESSMENT - GRODZIŃSKA-JURCZAK, MAŁGORZATA; KRAWCZYK, ALEKSANDRA; JURCZAK, ANNA; STRZELECKA, MARIANNA; RECHCIŃSKI, MARCIN; BOĆKOWSKI, MARIUSZ (Society Register, 2020)
Alarming plastic production growth worldwide reinforces the public debate about the prevailing environmental crisis, whereby single-use-plastic (SUP) items are considered as by far the most harmful to the environment and public health. Accordingly, European environmental policy aims at eliminating SUP. Recently, we presented a model of plastic governance that derives from a circular economy approach identifying and taking into consideration perspectives of different actors in the plastic governance, such as producers, wholesalers, shop keepers, consumers, citizen scientists, and academia. Our results illustrate that the vast majority of stakeholders cared for the natural environment and understood the need to phase out SUP from the global economy. We proposed that a knowledge brokerage, undertaken by scientists via means of citizen science, as the most effective method to implement elimination policy, as it provides stakeholders with knowledge on why and how to handle SUP issues. However, at the time of the global COVID-19 pandemic, a plastic governance model required a re-assessment. The perceived role of SUP has changed, as it reflects the health emergency. Namely, due to the health safety reasons stakeholders and consumers are requesting even more SUP than previously. Following up on our data gathered prior to the pandemic, we suggest that under the new circumstances health concerns outweigh the environmental concerns being determined by a shift in the value hierarchization. The paper discusses preliminary results.